The Interpretation Shift of Polygamy Verses in Surah an-Nisā’(4): 3 and Its Contextualization In the Contemporary Era (Interpretation Studies in the Classical, Medieval, Modern-Contemporary Era) - Zulyadain Zulyadain; Wely Dozan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The study of gender issues along with the dynamics of the times has been in the spotlight, especially the reviewers of Islamic interpretation and thought, gender issues are getting hotter so that the implications are for commentators to continue to do ijtihad so that interpretations are in accordance with the text and context. The gender issue is specifically contained in the Qur'an Surah an-Nisā' (4): 3, where this verse often has different interpretations of the classical, medieval, and modern-contemporary commentators. Specifically, the medieval-classical interpretation tends to understand the verse as legitimacy and a commandment to practice polygamy. But on the one hand, modern-contemporary thinking reads the verse more as a monogamy command rather than on the aspect of polygamy. This diversity becomes a necessity which is certainly caused by several factors that are the background for these commentators. The purpose of this article is to try to analyze the causes of a shift in interpretation and the factors behind the occurrence of a shift in interpretation, especially Surah an-Nisā' 4: 3 from the perspective of classical, medieval, to modern-contemporary commentators. This research is a library research with an approach descriptive analysis. The results of this study indicate that the medieval-classical interpretation of understanding the verse is due to the influence of patriarchal culture and ideology so that the text is often understood textually without dialogue between the text and reality However, the modern-contemporary interpretation of the verse does not refer to the aspect of polygamy even though it is essentially an order, but rather to the monogamous aspect, because contextual reading in understanding the text needs to have a dialogue by looking at its implications for social reality